(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
The need for archiving Sindhi literary tradition in India comes from the space of serving the Sindhi community and its literature divided by the partition of India. This region-less regional literature has been facing a lot of challenges. For instance, it has not thrived the way literatures from the other two partitioned territories (Punjab and Bengal) have because Sindhis did not get a land or a province they could call their own in India. It has also been divided by script in the sense that multiple scripts are in use and the practice of reading/writing in Sindhi itself is disappearing (Daswani, 1989. The digital archive project PG Sindhi Library is an attempt to make older books published in the early years of independent India accessible to the Sindhi community and those interested in South Asian Studies as well as to encourage readers to contribute their items to the library, or even build their own archives. This paper shares the archivist’s findings or lessons learned from the experience with the larger community of digital humanists working in archiving projects. The objective is also to integrate archival work with that of the researcher and theorise archiving from a practitioner’s point of view, given the need to reflect on the unique archival and digital needs of Global South.